A new personal and work cross-cultural adjustment model of malaysian professional expatriates in construction industry / Halmi Zainol ... [et al.] - Zainol, Halmi; A Tambi, Abdul Malek; Ali, Nor Eeda; Azman, Muhamad Azrul Azwan; Amir Ishak, Noor Roslinda; Haron, Norhazlan; Azami, Hazirah (2020)
The difficulty in adjusting to a new environment is among the issues that contribute to the poor performance of expatriates. What contributes to the success of an individual in a workplace is the psychosocial comfort that is prevalent in the new environment. Diversity of culture, race and religion in an organization is acceptable where there is tolerance. The aim of this study is to develop a new model of cross-cultural work adjustments for professional expatriates in Malaysia. Three stage review of previous studies involving identification of work adjustment elements, cross-cultural elements and conceptualising a proposed expatriate adjustment framework was adopted. The cross-cultural work adjustment model developed is hinged upon three pillars: personal adjustment factor, work adjustment factor and crosscultural adjustment. The findings of the study revealed that adjusting to the host's national custom or culture, religious practice, and cultural entertainment are among the factors that influence personal and work cross-cultural adjustments of expatriates. Organisations and related agencies could use the findings of the research to take necessary actions to reduce the propensity of professionals leaving their home companies abroad.